An Exponential Intuitionistic Fuzzy Framework for Sustainable Supplier Selection in Industrial Management (European Journal of Pure and Applied Mathematics, 2025)
Dealing with uncertainty and imprecision is critical in modern decision-making processes, particularly in multi-criteria situations. Exponential Intuitionistic Fuzzy Sets (EIFS) are a sophisticated mathematical framework that extends intuitionistic fuzzy sets by integrating an exponential function, improving its capacity to adequately capture ambiguity. This study investigates several EIFS operations, such as EIF intersection and union, which expand conventional set operations to accommodate partial and non membership NM degrees more flexibly. Furthermore, we look into crucial operations including simple difference, limited difference, disjoint sum, disjunctive sum, and Cartesian product, all of which play important roles in modelling uncertainty in decision processes. A case study on raw material purchase demonstrates how these processes might be applied. The decision-making system takes into account numerous providers, analysing aspects such as cost, quality, and delivery time with EIFS-based aggregation approaches. Using these activities, decision-makers may improve supplier performance, reduce risks, and optimise procurement strategies in unpredictable circumstances.